1989
DOI: 10.1128/aem.55.1.55-65.1989
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Population Development and Chemical Characteristics of Refuse Decomposition in a Simulated Sanitary Landfill

Abstract: Population development of key groups of bacteria involved in municipal refuse conversion to methane was measured from the time of initial incubation through the onset of methane production. Hemicellulolytic bacteria, cellulolytic bacteria, hydrogen-producing acetogens, and acetate-and H2-plus-CO2-utilizing methanogens were enumerated by the most-probable-number technique with media containing oat spelt xylan, ball-milled cellulose, butyrate, acetate, and H2 plus C02, respectively. Refuse decomposition was moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
100
1
6

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 310 publications
(113 citation statements)
references
References 33 publications
6
100
1
6
Order By: Relevance
“…As leachate is the result of liquid percolation through the site, it potentially provides a comprehensive sample of the landfill microbiota. Since the acquisition of colonized solid material from a landfill site is not possible, lab-scale landfill bioreactors have been used in previous studies of landfill microbiology (Barlaz et al, 1989;Burrell et al, 2004;McDonald et al, 2010). Here, two landfill leachate microcosms were constructed to facilitate the in situ colonization of cellulose substrates (dewaxed cotton string) for characterization of the microbial biofilms via PCR, qPCR and SEM ( Fig.…”
Section: In Situ Analysis Of Cellulose Degradation In Landfill Leachamentioning
confidence: 99%
“…As leachate is the result of liquid percolation through the site, it potentially provides a comprehensive sample of the landfill microbiota. Since the acquisition of colonized solid material from a landfill site is not possible, lab-scale landfill bioreactors have been used in previous studies of landfill microbiology (Barlaz et al, 1989;Burrell et al, 2004;McDonald et al, 2010). Here, two landfill leachate microcosms were constructed to facilitate the in situ colonization of cellulose substrates (dewaxed cotton string) for characterization of the microbial biofilms via PCR, qPCR and SEM ( Fig.…”
Section: In Situ Analysis Of Cellulose Degradation In Landfill Leachamentioning
confidence: 99%
“…Methanogenesis from cellulose is a stepwise process accomplished by consortia containing numerous species of bacteria (Gujer and Zehnder 1983). It has been shown that the rate of methane production in landfill is limited by the rate of polymer hydrolysis (Barlaz et al 1989). Therefore an understanding of those factors that contribute to the inhibition of hydrolysis of the most important polymer, cellulose, is vital for the most efficient exploitation of landfillderived renewable energy.…”
Section: Introductionmentioning
confidence: 99%
“…The degradation of organic matter in landfill sites generates methane which may be sufficient to be economically collected and used [1][2][3]. However, in many, particularly older or small sites, it is often uneconomical.…”
Section: Introductionmentioning
confidence: 99%